Genetic diversity and forensic characteristics of 15 autosomal short tandem repeats in Tibet highland and Guangdong lowland Han Chinese populations. (17th February 2019) - He, Guanglin; Gao, Bo; Guo, Jianxin; Su, Yongdong
Abstract: Background: Much attention has been paid to the genetic variants of microsatellites in East Asian populations; however, genetic diversity of high-altitude adaptation in Tibet Han remains largely uncharacterised. Aim: To profile DNA samples from 338 high-altitude adaptation Han Chinese individuals and 933 low-altitude living Han Chinese individuals for 15 autosomal STRs which are used for human identification purposes and to estimate the forensic parameters as well as explore the genetic relationships among 38 Chinese populations. Subjects and methods: Fifteen autosomal STR loci and amelogenin genes were amplified in 1271 individuals using the AmpFℓSTR ® Sinofiler™ PCR Amplification Kit. Allele frequencies and forensic parameters were calculated. Subsequently, population comparisons among 38 groups were analysed via principal components analysis, Reynolds genetic distance, neighbour-joining tree and multidimensional scaling plots. Results: In this study, no departures from Hardy-Weinberg equilibrium are identified in either Tibet or Guangdong Han populations after Bonferroni correction. The cumulative match probabilities are 3.1108 × 10 −19 in Guangdong Han and 6.2102 × 10 −19 in Tibet Han, and the combined probabilities of exclusion for trios are 0.99999948 and 0.99999936, respectively. Comprehensive population comparisons based on allele frequency distribution indicate that the Tibet Han population has a genetically close relationship with the surrounding population (Tibet Tibetan) and the Guangdong Han population has genetic affinity with southern Chinese populations. Conclusion: In general, genetic polymorphisms and forensic efficiency indicated that the 15 STRs studied are informative and polymorphic in both lowland and highland Han populations.